Fried Fish Ball “Patilo” Based on Catfish and Cowpea Flour as an Alternative Snack to Prevent Anemia in Adolescent Girls - Sarah Dzakirah Arham; Umi Mahmudah; Surmita; Nuniek Widyaningrum (Jurnal Gizi dan Dietetik, 2025)
Adolescent girls are one of the groups most vulnerable to iron deficiency anemia. Inadequate protein and iron intake is one of the contribute factors to anemia. Snack food are needed to help meet the daily nutritional requitments of adolescent girls. Catfish and cowpea flour are food ingredients rich in protein and iron. The combination of these two ingredients can be processed into a snack product such as Fried Fish Balls, which serve as an alternative snack as a source protein and iron. This study aimed to determine the effect of cathfish and cowpea flour formulations on the characteristics of “Patilo” Fried Fis Balls. This experimental study used a Completely Randomized Design (CRD) with cathfish and cowpea flour formulations of 90%:10%, 80%:20%, and 65%:35%, and an organoleptic assessment using a hedonic test was conducted with 30 semi-trained panelists. The hedonic test results showed significant differences (p<0,05) in color, taste, aroma, texture, and overall acceptance. Formula 1 was identified as the most preferred by the panelists. Proximate analysis revealed the nutritional value per serving (150 g) and its contribution to daily recommended intake: energy 209,83 kcal (10,4%), protein 16,78 g (27,2%), fat 2,16 g (3,2%), carbohydrates 30,79 g (10,5%) and iron 1,83 mg (14,4%). Additional fat incorporation may be needed to improve the product’s fat content.